2015
DOI: 10.1371/journal.pone.0139392
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of the Coleus R2R3 MYB-Type Proanthocyanidin Regulator Gene SsMYB3 Alters the Flower Color in Transgenic Tobacco

Abstract: Proanthocyanidins (PAs) play an important role in plant disease defense and have beneficial effects on human health. We isolated and characterized a novel R2R3 MYB-type PA-regulator SsMYB3 from a well-known ornamental plant, coleus (Solenostemon scutellarioides), to study the molecular regulation of PAs and to engineer PAs biosynthesis. The expression level of SsMYB3 was correlated with condensed tannins contents in various coleus tissues and was induced by wounding and light. A complementation test in the Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…Several results indicated that MYB and bHLH transcriptional factor families play a vital role in the regulation of tissue color (Umemura et al, 2013; Zhu et al, 2015). Gisbert et al (2016) showed that the regulatory genes ( MybC, Myc, and Wd ) was significantly decreased in the green color mutant in comparison with the WT eggplant.…”
Section: Discussionmentioning
confidence: 99%
“…Several results indicated that MYB and bHLH transcriptional factor families play a vital role in the regulation of tissue color (Umemura et al, 2013; Zhu et al, 2015). Gisbert et al (2016) showed that the regulatory genes ( MybC, Myc, and Wd ) was significantly decreased in the green color mutant in comparison with the WT eggplant.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of CTs have been demonstrated in only support the primary plant metabolism (Haslam, 1981). It is now well established that CT synthesis is under genetic control (Szczyglowski and Stougaard, 2008;Scioneaux et al, 2011;Cheynier et al, 2013;Escaray et al, 2014) and that expression depends on the plant species and plant parts (Larkin et al, 1997;Gebrehiwot et al, 2002;Abeynayake et al, 2012;Ferreyra et al, 2012;Hancock et al, 2012;Verdier et al, 2012;Cheynier et al, 2013;Harding et al, 2013;Mouradov and Spangenberg, 2014;Pérez-Díaz et al, 2014;Zhou et al, 2015;Zhu et al, 2015;Chezem and Clay, 2016).…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
“…All enzymes involved in the biosynthesis of the CT building blocks (i.e., flavan-3-ols) have been identified, apart from the elusive final condensing enzyme(s) (Harding et al, 2013). Two genes and several myeloblastosis (MYB) transcription factors (i.e., proteins with myeloblastosis DNAbinding domains that regulate CT synthesis) are responsible for the production of two of the flavan-3-ols (i.e., catechin and epicatechin; Ferreyra et al, 2012;Cheynier et al, 2013;Zhu et al, 2015;Chezem and Clay, 2016), but the genes and transcription factors for the other flavan-3-ols await identification. The MYB transcription factors from barrelclover (Medicago truncatula Gaertn.)…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 99%
“…The relative concentration of anthocyanins was determined following Christie et al (1994) and Zhu et al (2015) with minor modifications. Pulverized leaf blade tissue (1.0 g fresh weight) was homogenized in 12 ml of methanol containing 0.1 N HCL and maintained at 4°C for 4 h. Three repetitions were performed for each taxon.…”
Section: Determination Of Concentration Of Anthocyaninsmentioning
confidence: 99%